Flame Retardants:Polymer Blends, Composites and Nanocomposites - Visakh, P. M (Springer, 2015)
This book summarizes comprehensively many recent technical research accomplishments in the area of flame retardant research. It presents mainly flame retardant studies of polymer blends, composites and nano composites such as rubber, thermosets and thermoplastics. This book discusses different types of flame retardant using in polymers especially nano composites, as well as the role and chemistry.